That dream shall have a name : native Americans rewriting America - Moore, David L., 1951- (University of Nebraska Press, 2014)
"The founding idea of "America" has been based largely on the expected sweeping away of Native Americans to make room for EuroAmericans and their cultures. In this authoritative study, David L. Moore examines the works of five well-known Native American writers and their efforts, since the nation's early days, to redefine an "America" and "American identity" that includes Native Americans. That Dream Shall Have a Name focuses on the writing of Pequot Methodist minister William Apess in the 1830s; on Northern Paiute activist Sarah Winnemucca in the 1880s; on Salish/Me;tis novelist, historian, and activist D'Arcy McNickle in the 1930s; on Laguna poet and novelist Leslie Marmon Silko; and on Spokane poet, novelist, humorist, and filmmaker Sherman Alexie in the latter twentieth and early twenty-first centuries. Moore studies these five writers' stories about the conflicted topics of sovereignty, community, identity, and authenticity--always tinged with irony and often with humor. He shows how Native Americans have tried from the beginning to shape an American narrative closer to its own ideals, one that does not include the death and destruction of their peoples. This compelling work offers keen insights into the relationships between Native and American identity and politics in a way that is both accessible to newcomers and compelling to those already familiar with these fields."--